2013
DOI: 10.1158/1535-7163.mct-13-0041
|View full text |Cite
|
Sign up to set email alerts
|

SK-216, an Inhibitor of Plasminogen Activator Inhibitor-1, Limits Tumor Progression and Angiogenesis

Abstract: Plasminogen activator inhibitor-1 (PAI-1), which can be produced by host and tumor cells in the tumor microenvironment, is intimately involved in tumor progression. In the present study, to pursue the possibility that PAI-1 could be a therapeutic target in the management of malignancy, SK-216, a specific PAI-1 inhibitor, was orally administered to wild-type mice that were subcutaneously implanted or intravenously injected with either PAI-1-secreting Lewis lung carcinoma (LLC) or PAI-1-nonsecreting B16 melanoma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 38 publications
8
35
0
Order By: Relevance
“…In each mouse model of MPM using EHMES-10 cells or MSTO-211H cells, the antitumor effect of cisplatin was augmented by combining it with SK-216. In vitro, inhibition of PAI-1 by SK-216 suppressed migration and tube formation of HUVECs induced by bFGF, PDGF-BB, and HGF, as well as by VEGF, as reported previously (31).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In each mouse model of MPM using EHMES-10 cells or MSTO-211H cells, the antitumor effect of cisplatin was augmented by combining it with SK-216. In vitro, inhibition of PAI-1 by SK-216 suppressed migration and tube formation of HUVECs induced by bFGF, PDGF-BB, and HGF, as well as by VEGF, as reported previously (31).…”
Section: Discussionsupporting
confidence: 88%
“…6C and E, however, SK-216 was found to inhibit both migration and tube formation of HUVECs induced by bFGF, PDGF-BB, or HGF in a dose-dependent manner. A similar inhibitory effect of SK-216 on migration and tube formation of HUVECs was demonstrated in our previous study using VEGF as the inducer (31).…”
Section: Sk-216 Inhibited Migration and Tube Formation Of Huvecs Indusupporting
confidence: 86%
See 2 more Smart Citations
“…21 Masuda et al suggested that regardless of the levels of PAI-1 in the tumor, the systemic administration of SK-216, a specific PAI-1 inhibitor, exerts an antitumor effect through its interaction with host PAI-1 in PAI-1-secreting Lewis lung carcinoma or PAI-1 nonsecreting B16 melanoma cells. 22 It was reported that serine protease uPA and matrix metalloprotease (MMP) 2/MMP-9) play an important role in glioblastoma multiform growth in rat model. 23 Halamkova et al examined the expression of uPA, uPAR, PAI-1, and PAI-2 in tumor tissue and studied the plasma levels of PAI-1 before and after the initiation of therapy in patients with colorectal carcinoma in relationship with the grade of tumor and the treatment response.…”
Section: Discussionmentioning
confidence: 99%